2015
DOI: 10.18466/cbujos.96235
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of corrosion behavior of the AA5754 aluminum alloy joined using friction stir welding method

Abstract: Friction stir welding (FSW) between 2 mm thickness AA 5754 aluminum alloy sheet was researched in the current research. The welded joints were qualified by its aspects, microstructural ,mechanical features and corrosion behavior at cell temperature. The effect of the conical tool geometry on the FSW AA5754 are investigated over potentiodynamic polarization, open circuit potential (OCP) monitoring, test of the susceptibility to corrosion, micro-hardness and tension tests. The thermomechanically affected zones a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…95-196.26 MPa and elongation values between 10.8-14.5%. They reported that tensile damage has occurred in the thermomechanically affected zone [15]. In this study, Tensile strength values of AA5754-AA5754 joints were found to close to each other in despite of increasing heat input (Figure 3b), due to the non-heat treatable characteristic of AA5754 and working principle of CMT welding.…”
Section: Tensile and Bending Testssupporting
confidence: 55%
See 1 more Smart Citation
“…95-196.26 MPa and elongation values between 10.8-14.5%. They reported that tensile damage has occurred in the thermomechanically affected zone [15]. In this study, Tensile strength values of AA5754-AA5754 joints were found to close to each other in despite of increasing heat input (Figure 3b), due to the non-heat treatable characteristic of AA5754 and working principle of CMT welding.…”
Section: Tensile and Bending Testssupporting
confidence: 55%
“…Fracture surface with fine dimples indicates the ductile characteristic of AA5754 (Figure 4b). Mindivan et al (2015) joined the 2mm thick AA5754 plates with friction stir welding (1600rpm, 125mm/min). They obtained tensile strength values between 189.…”
Section: Tensile and Bending Testsmentioning
confidence: 99%
“…According to microstructural, mechanical, and residual stress tests of four Al alloys AA 5154, thermal input rather than tool deformation afects welding parameters. To better understand the impacts of postweld heat treatment on 2219-O aluminium alloy microstructure and mechanical characteristics, Mindivan et al [6] conducted a series of tests, tensile tests of heattreated regions increase as solution temperature rises, up to 260% greater than the base metal's (BM) maximum allowable tensile strength.…”
Section: Introductionmentioning
confidence: 99%
“…The EN AW-5754 (AlMg3) aluminum alloy was selected in the present work because of great interest in the automobile and aircraft industries as well as offshore construction applications due to its high specific strength and low density. In these applications materials are exposed to the marine environment that has a large presence of airborne salt particles and experiences a cyclic change in temperature [ 17 , 18 ]; hence the selection of EN AW-5754 due to its outstanding corrosion resistance to seawater and industrially polluted atmosphere [ 19 , 20 , 21 ]. Aluminum alloys are generally passive materials and pose a good corrosion resistance when exposed to neutral aqueous solutions [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that AA5754 alloy has better corrosion resistance in NaCl solution than pure aluminum due to the small fraction of iron present in aluminum [ 22 ]. It is also found that in AA 5754 aluminum alloy FSW joints TMAZ is most susceptible and HAZ is the most resistant to corrosion [ 20 ].…”
Section: Introductionmentioning
confidence: 99%